Kebijakan Tarif Ekspor Tinggi Amerika Serikat dan Dampaknya bagi Perekonomian Indonesia: Suatu Narrative Review - Adi, Tosan Surya; Artha, Bhenu (Indonesia Economic Journal, 2026)
The United States' protectionist policies, culminating in the "Liberation Day" announcement on April 2, 2025, have significantly altered the global trade landscape. This research aims to analyze the U.S. high export tariff policy and its substantive impact on the Indonesian economy using a narrative review method. The results indicate that the implementation of a 32% tariff on Indonesian products poses serious macroeconomic challenges, particularly for the textile, electronics, furniture, and palm oil sectors. The palm oil sector recorded a 22.5% decrease in export value, while national GDP growth is projected to slow from 5.20% to 5.03%. Theoretically, U.S. policies are driven by neo-mercantilist views utilizing domestic legal instruments (Sections 301 and 232) to justify protectionism on national security grounds. Indonesia responds through a five-pillar strategy encompassing trade diplomacy, market diversification via RCEP, and regulatory reforms to enhance manufacturing competitiveness. This study concludes that structural transformation toward high value-added economies is crucial for Indonesia to navigate global economic fragmentation and the erosion of the multilateral trading system